Long-term cardiovascular disorders in the STOX1 mouse model of preeclampsia - Miralles, Francisco; Collinot, Hélène; Boumerdassi, Yasmine; Ducat, Aurélien; Duché, Angéline; Renault, Gilles; Marchiol, Carmen; Lagoutte, Isabelle; Bertholle, Céline; Andrieu, Muriel; Jacques, Sébastien; Méhats, Céline; et al. (Scientific reports, 2019)
Adverse long-term cardiovascular (CV) consequences of PE are well established in women. However, the mechanism responsible for that risk remains unknown. Here, we mated wild-type female mice of the FVB/N strain to STOX1A-overexpressing mice to mimic severe PE and investigated the long-term consequences on the maternal cardiovascular system. Ultrasonography parameters were analyzed in mice before pregnancy and at 3 and 6 months post-pregnancy. At 6 months post-pregnancy, cardiac stress test induced by dobutamine injection revealed an abnormal ultrasonography Doppler profile in mice with previous PE. Eight months post-pregnancy, the heart, endothelial cells (ECs) and plasma of females were analyzed and compared to controls. The heart of mice with PE showed left-ventricular hypertrophy associated with altered histology (fibrosis). Transcriptomic analysis revealed the deregulation of 1149 genes in purified ECs and of 165 genes in the hearts, many being involved in heart hypertrophy. In ECs, the upregulated genes were associated with inflammation and cellular stress. Systems biology analysis identified interleukin 6 (IL-6) as a hub gene connecting these pathways. Plasma profiling of 33 cytokines showed that, 8 of them (Cxcl13, Cxcl16, Cxcl11, IL-16, IL-10, IL-2, IL-4 and Ccl1) allowed to discriminate mice with previous PE from controls. Thus, PE triggers female long-term CV consequences on the STOX1 mouse model.